An In-Vivo Herb Drug Interaction Study of Some Anticancer Drugs With Herbal Extract In Albino Rats - Rajni Yadav; Amit Roy; Trilochan Satapathy (International Journal of Medical Toxicology and Legal Medicine, 2024)
Herbal supplements are commonly taken in conjunction with standard anticancer chemotherapy, heightening the risk of clinically relevant herb–drug interactions. Holy Basil (Tulsi; Ocimum sanctum) is a commonly utilized medicinal plant with antioxidant, immunomodulatory, and anti-inflammatory properties; yet, its impact on the pharmacokinetics of cytotoxic medications remains inadequately defined. This research examines the pharmacokinetic interactions between ethanolic Tulsi leaf extract and two widely prescribed anticancer drugs—cisplatin and paclitaxel—utilizing an albino rat model. Adult Wistar rats underwent pre-treatment with Tulsi extract (200 mg/kg/day, orally) for seven days before to a single-dose infusion of cisplatin (6 mg/kg, intraperitoneally) or paclitaxel (10 mg/kg, intraperitoneally). Sequential blood samples were obtained over a 24-hour duration, and plasma drug concentrations were measured utilizing proven HPLC–UV techniques. Pharmacokinetic parameters were determined by non-compartmental analysis (NCA). The co-administration of Tulsi extract significantly diminished the systemic exposure of both anticancer agents. Cisplatin demonstrated a reduction in Cmax (−27.8%) and AUC0–∞ (−31.4%), accompanied by greater clearance and a decreased half-life, indicating improved elimination. Paclitaxel had a same trend, demonstrating decreases in Cmax (−24.3%), AUC0–t (−28.9%), and AUC0–∞ (−30.5%). The concentration–time profiles for both medications exhibited diminished peak concentrations and expedited drop in Tulsi-treated groups, indicative of reduced absorption and enhanced clearance. The data demonstrate a substantial pharmacokinetic herb-drug interaction, likely influenced by Tulsi’s impact on membrane permeability, modification of metabolic enzymes, or activity of efflux transporters.Tulsi extract significantly modified the pharmacokinetics of cisplatin and paclitaxel in vivo, potentially diminishing their bioavailability and therapeutic effectiveness. Exercise caution when consuming Tulsi supplements during chemotherapy. Additional mechanistic and clinical investigations are necessary.